Failures of the Sociological Imagination: Trump, "Brexit, " and the Politics of Unfinished Conflict. Issue 2 (2nd April 2020) - Curtis, Jennifer
ABSTRACT: In 2016, Trump's presidential campaign and the Leave campaigns in the U.K. "Brexit" referendum used racist messaging strategies. This article considers how these messaging strategies exploited the politics of unfinished conflict in both the U.S. and U.K. Based on ethnographic fieldwork in Springfield, Missouri and Belfast, Northern Ireland, the article considers how history shaped reception of this rhetoric in my fieldsites. It concludes that cynical messaging strategies weaken democracy, renew violence, and reproduce systemic inequalities, utilizing C. Wright Mills' and Zora Neale Hurston's work as models for public sociology to analyze and address the politics of unfinished conflict.